A deep dive into research trends in sports journalism - Hanny Hafiar; Priyo Subekti; Ika Merdekawati Kusmayadi; Davi Sofyan; Kholidil Amin (Social Sciences and Humanities Open)
Sports and media have developed into industries. This development forces sports journalism to prepare for various changes, such as adapting to digital transformation. The availability of sources and ways of processing news involving digital media have changed the landscape of sports journalism to become more complex. This complexity has attracted the attention of researchers and driven the rapid growth of journalism studies in recent years. It shows the existence of various urgent challenges that require immediate attention. This study aims to determine research trends related to sports journalism by analysing 363 documents in the Scopus database published from 1976 to 2023 and using bibliometric analysis. The result shows that 2022 is the year with the highest number of published articles. Scholars from various affiliations and countries actively research this theme and publish it in a number of the most prolific journals. Keyword mapping produced seven clusters, and findings regarding the evolution of research themes show the increasingly strong interconnection of sports journalism with digital technology, which is starting to give rise to contemporary terminology such as data journalism, digital media, and artificial intelligence. These findings contribute to future research as a guide for researchers in developing contemporary studies related to sports journalism. As for practitioners, the results of this study can be used to prepare and develop sports communication strategies and tactics through the use of appropriate media. The limited number of databases used in this study opens up opportunities for further research in the future to gain sustainable knowledge. Likewise, the addition of new articles published in this field in the coming years will likely produce new and different findings from those presented in this research.